Realism, the United States, and China: Strategic Comparison and Projection in the Pacific (Journal of the Spanish Institute for Strategic Studies, 2025)
The strategic competition between the United States and China in the Pacific is addressed from the perspective of realism, a theory that highlights power, national interest, and security in foreign policy. Despite political and ideological differences, both actors seek to maximize their influence in an international environment marked by uncertainty. The United States, in an effort to maintain its regional hegemony, has strengthened its alliances and military presence to curb China’s rise. Meanwhile, China is expanding its military, technological, and economic capacity, challenging the established order and positioning itself as a systemic challenge to U.S. hegemony. The Pacific Ocean thus becomes the epicenter of a competition that reflects growing tensions between both powers, where the balance of power is at stake in a context of increasing rivalry. Understanding these geopolitical, technological, and diplomatic dynamics is key to analyzing the development of this competition in a critical region of the international system.
Keywords: Balance of power; Strategic competition; Geopolitics; Security; Rivalry